Laboratório de eletrônica: uma proposta experimental e virtual como alternativa didática para circuitos elétricos do tipo retificador a diodo - CARDOSO, Darlan Holanda (2021)
The present work elaborated a pedagogical strategy and a didactic alternative that could arouse greater interest of the students in physics subjects and more specifically in electronics, in order to overcome the challenges that the subject proposes, in this way we propose the realization of real and virtuais experimentais scripts for the electronics laboratory, that is, an experimental and virtual proposal as a didactic alternative for electrical circuits of the diode rectifier type. Therefore, a pedagogical material was created to help the student to develop a diode rectifier circuit experiment, which contains all the necessary information and challenges for its execution. (i) The real proposal was developed to be carried out in the Experimental Physics Teaching Laboratory. (ii) The virtual proposal was developed to run in the virtual simulator “Falstad Circuit Simulator Applet. The material gives an understanding of the atom, highlighting their behavior when they are placed in front of a voltage, showing that the materials have electrical properties. This work aims to relate theory to everyday situations through study scripts for real and virtual experimental activities, where it was sought to formalize the materials so that lectures on Diode Rectifier Circuits were not necessary. From this, voltage comparisons of the values obtained by the simulator were made, along with experimental measurements and calculations, and we concluded that the experimental electronics present in the daily life of the technological world can broaden different aspects of the view of science, making individuals they can also propose solutions to daily problems or perhaps help to discover new relationships in the world of work and science and technology and have as their target audience, third-year high school students and undergraduate students who have the Experimental Electronics subject in their curriculum basis.